Eksistensi Perempuan di Parlemen : Studi Kesetaraan Gender di Dewan Perwakilan Rakyat Daerah Kota Palangkaraya - Ester Sonya Ulfaritha Lapalu; Elizabeth (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2021)
Today, the problem of gender inequality in Indonesia can still be found in various spheres of life, both social and practical politics. Inequality eventually gives rise to various forms of injustice and gender equality. This is still happening in the structure of parliamentary representative institutions in our country. The demand for fulfilling a minimum of thirty percent (30%) of women's representation in practical politics, especially in the legislature has now become one of the crucial and fundamental problems. Amendment to Law No. 8 of 2008 became Law no. 7 of 2017 concerning the General Election of Members of the House of Representatives, Regional Representatives Council and Regional People's Representative Council, which every year opens a space or way of openness for women to be able to participate in practical political stages which are increasingly dynamic in reality.